Rafael Roncagliolo in the Chancellor's office - Rojas Samanez, Fernando (2021)
The death of Rafael Roncagliolo has generated a wide impact in different sectors and national and international institutions, which regretted his disappearance and highlighted his extensive political, social and academic career, especially in the search for consensus in favor of democracy, institutionality and transparency in the activity public and private policy. The event held on Thursday, May 14, convened by the National Agreement and headed by the President of the Republic, constituted in my opinion, an unprecedented civil society public tribute event. There was no excesses, it was a sober and felt act that, in the current days in the country, acquired greater meaning and that can be condensed into a few simple words: will, dialogue, respect, governability, democracy, commitment and that converged on one objective: thePeru and its citizens.